Native Berries of Chile: A Comprehensive Review on Nutritional Aspects, Functional Properties, and Potential Health Benefits - Bustos-Cerda, R; Vera-Vera, C; Florez-Mendez, J (Springer, 2021)
In recent years, the use of native berries has increased, since the presence of elevated levels of bioactive compounds and, consequently compounds that provide beneficial effects for human health has been shown. This study reviews the nutritional aspects, phytochemical composition, and biological activities of native berries of Chile, specifically Ugni molinae, Berberis microphylla, Fragaria chiloensis, Aristotelia chilensis, and Ribes spp. These species are rich in bioactive compound with several health promoting effects. The most significant health benefits have been attributed to phenolic compounds, specifically anthocyanins, which have potential protective roles against cancer and cardiovascular diseases. This paper discusses the biological activity of those compounds, in particular their antioxidant properties, the bioaccessibility and bioavailability of phenolic compounds and their health-promoting properties to emphasize the importance of native berries from Chile in healthy diets. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.